Comparative Use of Live Feed in African Catfish Larvae Raising - Yakhshibekov G.R; Mullabaev N.R; Kamilov B.G; Ayasov.Kh.G (Zien Journals, 2023)
In October 2023, for 15 days, in 60-liter plastic containers with aeration at a temperature of 25- 26 ° C, African catfish larvae were fed with live food: zooplankton (collected in the Tuyabuguz reservoir), Daphnia magna, common tubifex and aulophorus. The fry grew to an average of 0.63 g, 0.87 g, 1.13 g and 1.07 g, respectively. The recovery was 58%, 61%, 71.5% and 45.6%, respectively. Indicators of growth and quality of feed are given.
Keywords: African catfish; Clarias Garie Pinus; fish feeding; live feed